Выражение (x+2)²-(x+7)² = (x-15)²-(x+3)² = (3m-2)²-(2m+1)² = (2k+5)²-(2k-1)² =

kateKos1 kateKos1    3   01.06.2019 17:10    0

Ответы
elizavetaliza89 elizavetaliza89  02.07.2020 19:20
Выражение: (x+2)^2-(x+7)^2=x^2+4*x+4-(x^2+14*x+49)= -10*x+4-49= -10*x-45
ответ: -45-10*x
Выражение: (x-15)^2-(x+3)^2=x^2-30*x+225-(x+3)^2=-30*x+225-6*x-9=-36*x+216
ответ: 216-36*x
Выражение: (3*m-2)^2-(2*m+1)^2=9*m^2-12*m+4-(2*m+1)^2=5*m^2-12*m+4-4*m-1=5*m^2-16*m+4-1=5*m^2-16*m+3
ответ: 5*m^2-16*m+3
Выражение: (2*k+5)^2-(2*k-1)^2=4*k^2+20*k+25-(2*k-1)^2=20*k+25+4*k-1=24*k+24
ответ: 24+24*k
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика